Capacity Building for Migrant Worker Parents in Parenting Skills at the Gombak Utara Community Learning Centre, Kuala Lumpur, Malaysia - Erhamwilda; Hakim, Arif; Afrianti, Nurul; Nuraini, Nabilah; Saepudin, Aep (Divisi Riset, Lembaga Mitra Solusi Teknologi Informasi (L-MSTI), 2025)
Indonesian migrant workers in Malaysia encounter ongoing obstacles in securing formal education for their children. These barriers stem primarily from unresolved citizenship status and insufficient documentation. While Community Learning Centers (CLCs) offer basic education for children aged eight and above, early childhood development support remains inadequate. Limited parental knowledge and mothers' demanding work schedules further compound these challenges. This community service program aims to strengthen parenting skills among migrant worker parents, empowering them to better support their children's development. The initiative encompasses structured parenting workshops and play-based learning sessions designed to enhance parent-child interactions while fostering children's self-confidence and learning motivation. The program's primary beneficiaries are migrant worker parents and their children enrolled at the Gombak Utara Community Learning Center in Kuala Lumpur, Malaysia. The intervention employs the Participatory Rural Appraisal (PRA) approach, emphasizing active community participation and collaborative problem-solving. Findings demonstrate enhanced maternal understanding of quality parenting practices through nurturing interactions, play activities, supportive home learning environments, appropriate parenting approaches, and Islamic values integration. Participants exhibited notable shifts in parenting attitudes, evidenced by heightened awareness in evaluating their previously employed parenting methods.